2012
DOI: 10.1089/omi.2011.0066
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differential Gene Expression Profiles in Placentas from Preeclamptic Pregnancies Versus Normal Pregnancies by DNA Microarrays

Abstract: The purpose of this study was to perform a comprehensive analysis of gene expression profiles in placentas from preeclamptic pregnancies versus normal placentas. Placental tissues were obtained immediately after delivery from women with normal pregnancies (n = 6) and patients with preeclampsia (n = 6). The gene expression profile was assessed by oligonucleotide-based DNA microarrays and validated by quantitative real-time RT-PCR. Functional relationships and canonical pathways/networks of differentially-expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 39 publications
3
33
0
2
Order By: Relevance
“…These results suggest decreased tolerogenic activity of pMw during CA. This finding may be related to the increased expression of WNT pathway genes, which are associated with inflammatory responses, and a recent study reported aberrant regulation of the WNT pathway at the transcriptional level during preeclampsia (58). Importantly, we found that pMw from CA patients were unable to mature in MGCs but that supernatant from cultured control trophoblasts was able to partially restore the ability of pMw to differentiate into MGCs.…”
Section: Discussionsupporting
confidence: 50%
“…These results suggest decreased tolerogenic activity of pMw during CA. This finding may be related to the increased expression of WNT pathway genes, which are associated with inflammatory responses, and a recent study reported aberrant regulation of the WNT pathway at the transcriptional level during preeclampsia (58). Importantly, we found that pMw from CA patients were unable to mature in MGCs but that supernatant from cultured control trophoblasts was able to partially restore the ability of pMw to differentiate into MGCs.…”
Section: Discussionsupporting
confidence: 50%
“…As a first step toward class discovery of PE pathology, we performed an aggregated analysis of 7 previously published human PE placental microarray data sets 4,5,[28][29][30][31][32] using unbiased/ unsupervised multivariate clustering techniques. 13 Our methods, which improve on similar approaches used for the molecular subclassification of tumors in the oncology field, 33,34 blindly group samples based solely on similarities in gene expression, independent of clinical characteristics.…”
Section: 3mentioning
confidence: 99%
“…From the Research Centre for Women's and Infants' Health BioBank, we collected 157 placenta samples (BioBank samples) with detailed clinical data from a range of hypertensive and normotensive states. To increase our sample size, the BioBank samples were then combined with the 7 previously published placental microarray data sets 4,5,[28][29][30][31][32] (Table S1 in the online-only Data Supplement) that we have previously analyzed in aggregate (Aggregate samples). 13 The final combined data set contained 330 placentas (157 PE and 173 non-PE) and expression values for 14 651 genes found in common across all original microarray platforms.…”
Section: Assembly Of the Combined Data Setmentioning
confidence: 99%
“…Several gene expression studies (Lapaire et al, 2012;Louwen et al, 2012;Meng et al, 2012;Zhou et al, 2013) have been conducted to investigate expression differences between preeclampsia patients and healthy controls. The major challenge for microarray analysis is to develop a suitable statistical model to deal with the small sample number and large number of genes.…”
Section: Introductionmentioning
confidence: 99%